Political awareness among the full time diploma students in UiTM Samarahan Campus / Nurul Muna Mohd. Shapri … [et.al.] - Mohd. Shapri, Nurul Muna; Habib, Nor Asma Warnee; Adenan, Amie Azreen; Mukhti, Noranida; Ajat, Norehan (2005)
This research is about the political awareness among the Uitm students. From the analysis that we have done, we realized that Uitm students are not really know about the political situation in their country. They also do not have the political awareness among themselves. We have deals with our research proposal since we are in Part 5 for intake June2004-0ctober 2004 until we are in Part 6 for intake November 2004-April 2005. Our proposal contains 5 Chapter which also included the recommendation, bibliography, appendix, Gantt chart and also budget estimation. The first chapter in our proposal are about the introduction which it contains the background, scope, objective and hypothesis. The second chapter about the literature review which it support out research and also as our references. The third chapters are about the research methodology that we used to analyze the data that we have collected. The fourth chapters are about the data analysis and the finding for our research.